Landscape Ecology The Influences of Land Use and Anthropogenic Impacts of Landscape Creation - Almusaed, Amjad (IntechOpen, 2016)
This book has been written to present major and efficient applications in landscape ecology, as well as to propose a solid action for this category of topics. The book aims to illustrate various treatment methods of the land-use models impact on landscape ecology creation. The book is divided into three parts: Part I: Ecological interpretation of land-use act - in this part, ecosystem and land use turn out to be a significant factor in the process of creating an ecological landscape. Part II: Landscape district in applied ecological analysis - this part attempts to illustrate the best possible model of analysis integrated with landscape in practical case studies. Part III: The anthropogenic impacts on landscape creation - this part discusses the human impact on landscape creation.